Vowel variability in elicited versus spontaneous speech: Evidence from Mixtec. (January 2015) - DiCanio, Christian; Nam, Hosung; Amith, Jonathan D.; García, Rey Castillo; Whalen, D.H.
Abstract: This study investigates the influence of speech style, duration, contextual factors, and sex on vowel dispersion and variability in Yoloxóchitl Mixtec, an endangered language spoken in Mexico. Oral vowels were examined from recordings of elicited citation words and spontaneous narrative speech matched across seven speakers. Results show spontaneous speech to contain shorter vowel durations and stronger effects of contextual assimilation than elicited speech. The vowel space is less disperse and there is greater intra-vowel variability in spontaneous speech than in elicited speech. Furthermore, male speakers show smaller differences in vowel dispersion and duration across styles than female speakers do. These phonetic differences across speech styles are not entirely reducible to durational differences; rather, speakers also seem to adjust their articulatory/acoustic precision in accordance with style. Despite the stylistic differences, we find robust acoustic differences between vowels in spontaneous speech, maintaining the overall vowel space pattern. While style and durational changes produce noticeable differences in vowel acoustics, one can closely approximate the phonetics of a vowel system of an endangered language from narrative speech. Elicited speech is likelier to give the most extreme formants used by the language than is spontaneous speech, but the usefulness of phonetic data from spontaneous speech has still been demonstrated. Abstract : Highlights: Vowel dispersion and variability examined for elicited and spontaneous speech in Yoloxóchitl Mixtec. Strong effects of speech style, duration, and gender observed. Speech style emerged as an effect independent from durational differences inherent to style. Despite strong patterns of vowel undershoot in spontaneous speech, the vowel space remained distinct across speakers. One can approximate formant values of elicited speech from spontaneous speech, though the styles remain somewhat distinct.